Design, Kinematic Analysis, and Scaled Prototype Validation of a Pneumatic Ejection Mechanism for Supersonic Re-Entry Capsule Testing - Alfan Firmansyah Aditya Aditya; Bagus Wicaksono; Akhmad Mukhlisin; Nur Hadi Ardiyanto; Rajni Rizkia Sirat; Muhammad Rafi Akbar Salahudin; Afzalurrohman Abdullah; Alfin Mardiansyah; Muchammad Rifki Sistiawan; Rajib Alamsyah; Rahmat Dani Sulistyo; Ade Firmansyah; Luthfy Iqbal Musthofa; Yoga Aditiya Dwi Syah Putra; Ahmad Yusuf Maulana; Pandu Priyo Jatmiko; Muhammad Thoriq Akmal Aliansyah; Johnson Fernando; Prayogi Dwi Kuncoro; Diah Ayu Suci Kinasih; Fajrul Falah (Akademi Inovasi Indonesia, 2025)
High-altitude free-flight tests require release mechanisms capable of placing sub-scale re-entry capsules into a clean supersonic freestream while minimizing wake-induced attitude perturbations. This study presents AERO, a compact pneumatic ejection mechanism developed to support NASA SPEED-class capsule-release requirements as a scientific contribution to re-entry testing technology. The method combined wake-clearance interpretation, first-order kinematic sizing, pneumatic force analysis, CAD-based packaging, manufacturability assessment, and scaled prototype testing. A two-projectile-length clearance distance of 1.33 m was adopted, giving a required initial velocity of 5.11 m/s for a 0.5 s separation target. The full-scale analytical model predicted an ejection velocity of 5.2 m/s and a 0.44 s separation time at 0.5 MPa; increasing the operating pressure to 1.5 MPa increased the velocity to 9.7 m/s and reduced the separation time to 0.15 s. A 30% scale prototype using a 32 g Genesis Firefly capsule model showed a pressure-dependent height response, increasing from 63.0 cm at 0.2 MPa to 136.8 cm at 0.6 MPa. These findings provide analytical and scaled-prototype evidence that a pressure-tunable pneumatic architecture with a balancing hugger can support rapid, repeatable, and geometry-adaptable capsule ejection; flight-representative performance remains to be validated.